`It`s not about disability, I want to win as many medals as possible`: The social construction of disability in high-performance coaching - Townsend, R. C.; Huntley, T.; Cushion, C. J.; Fitzgerald, H. (International Review for the Sociology of Sport, 2020)
This article draws on the theoretical concepts of Pierre Bourdieu to provide a critical analysis of the social construction of disability in high-performance sport coaching. Data were generated using a qualitative cross-case comparative methodology, comprising 18 months of ethnographic fieldwork in high-performance disability sport, and interviews with coaches and athletes from a cross-section of Paralympic sports. We discuss how in both cases `disability` was assimilated into the `performance logic` of the sporting field as a means of maximising symbolic capital. Furthermore, coaches were socialised into a prevailing legitimate culture in elite disability sport that was reflective of ableist, performance-focused and normative ideologies about disability. In this article we unpack the assumptions that underpin coaching in disability sport, and by extension use sport as a lens to problematise the construction of disability in specific social formations across coaching cultures. In so doing, we raise critical questions about the interrelation of disability and sport.